2014
DOI: 10.1080/14926156.2014.990171
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Anxiety and the Meaning of Participation in/for Science Fairs: A Canadian Case

Abstract: Although anxiety is a significant emotional element of formal school science, little is known about how anxiety is originated and managed in the context of science fairs. The purpose of the present study was to investigate how a group of students in Grades 7 to 12 discursively (re)produce anxiety and its management from the perspective of their participation in a national science fair competition in Canada. Based on the analysis of participant's talk during a focus group interview, our findings suggest that pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…This type of logical thinking, planning, and problem solving is an essential part of any career in science, technology, engineering, and math (STEM) and can also be a powerful tool outside these fields. Despite the importance of carrying out an independent scientific exploration, the science fair project is often met by strong resistance or anxiety from the students . The Reverse Science Fair (RSF) was developed to motivate high school students to engage in science by initiating informal conversations with graduate student researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of logical thinking, planning, and problem solving is an essential part of any career in science, technology, engineering, and math (STEM) and can also be a powerful tool outside these fields. Despite the importance of carrying out an independent scientific exploration, the science fair project is often met by strong resistance or anxiety from the students . The Reverse Science Fair (RSF) was developed to motivate high school students to engage in science by initiating informal conversations with graduate student researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of carrying out an independent scientific exploration, the science fair project is often met by strong resistance or anxiety from the students. 1 The Reverse Science Fair (RSF) was developed to motivate high school students to engage in science by initiating informal conversations with graduate student researchers. The researchers serve as role models who can explain how science is carried out and what excites them to do their research.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because of these reasons, scholars need to identify the causes of science anxiety to develop targeted measures. Experiencing higher levels of anxiety can negatively impact one's working memory, hinder information processing, and impede problem-solving skills, all of which are crucial components for succeeding in STEM fields (Gonzalez et al, 2019;Reis et al, 2014). When students face anxiety-related cognitive obstacles, they may struggle to comprehend, retain, and apply scientific knowledge (Meaders et al, 2020).…”
Section: / 11mentioning
confidence: 99%
“…In addition, science anxiety can harm a student's academic achievement by causing a lack of self-efficacy and intrinsic motivation (Henschel, 2021;Moeller et al, 2015;Reis et al, 2014). Therefore, it is crucial to recognize both the cognitive and affective dimensions of science anxiety and develop effective strategies to alleviate it, promoting a positive STEM learning environment (Megreya et al, 2021).…”
Section: / 11mentioning
confidence: 99%
“…The anxiety created by a science fair 5 can be helpful for the students. This study showed that science fairs helped kids realize where the anxiety comes from and that after going to many science fairs they can better handle the stress of presenting."…”
Section: Advantages Of Science Fairsmentioning
confidence: 99%